New security issues in Northern Europe the Nordic and Baltic states and the ESDP / edited by Clive Archer - Archer, Clive (Routledge/University Association for Contemporary European Studies series, 2008)
Analyzes the Nordic and Baltic states' relationship with the European Security and Defence Policy (ESDP). This work offers a general background to the EU's ESDP, the strategic situation of Northern Europe, the security and defence policy issues faced by the states, also outlining the theoretical considerations concerning security in the region.